Evaluation on Antioxidant Effect of Xanthohumol by Different Antioxidant Capacity Analytical Methods - Xiu-Li Zhang; Yong-Dong Zhang; Tao Wang; Hong-Yun Guo; Qi-Ming Liu; Hai-Xiang Su (Journal of Chemistry)
Several assays have been frequently used to estimate antioxidant capacities including ABTS•+, DPPH, and FRAP assays. Xanthohumol (XN), the major prenylated flavonoid contained in beer, witnessed various reports on its antioxidant capacity. We systematically evaluated the antioxidant activity of XN using three systems, 2,2,-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS•+) scavenging assays, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical assays, and ferric reducing antioxidant power (FRAP) assays. The results are expressed as Trolox equivalent antioxidant capacity (TEAC). The TEAC of XN was 0.32±0.09 μmol·l−1 by the ABTS assay and 0.27±0.04 μmol·l−1 by the FRAP. Meanwhile, the XN did not show obviously scavenging effect on DPPH radical reaction system. These results showed that different methods in the evaluation of compound antioxidant capicity, there may be a different conclusion.